KETERBACAN BAHAN AJAR SMA/SMK KELAS X PADA BAB VIII MENDALAMI PUISI DAN RELEVANSINYA DENGAN PEMAHAMAN SISWA - Alin Karlina; Dheni Harmaen; Marlia (STKIP Subang, 2022)
Teaching and learning activities in schools are not uncommon to find an obstacle in understanding a material in teaching materials. Based on the data obtained by the researchers related to the revised 2017 edition of the Indonesian language textbook for class X, especially regarding the material for studying poetry in chapter VIII, it was found that students had difficulty understanding the contents of the diction as outlined in poetry verses and students had difficulty in concluding the overall meaning of the diction contained in the text of the poem. The purpose of this study is to show and describe the level of readability of poetry texts in the revised 2017 edition of Indonesian textbooks, and to describe the relevance of poetry texts in class X to students' understanding. Qualitative descriptive is the approach used in this research process. Readability analysis using Fry's graphic formula, discourse text of poetry J1